(untitled) (Ozone Therapy Global Journal, 2016)
The vein-lymphatic insufficiency has a high repercussion in the population that suffers it. It is as an important social problem and due to their chronicity these patients have a permanent contact with the health services. The sequels of the chronic insufficiency can go from varicotrombosis, chronic ulcerations, deformities, until the loss of an extremity. Their treatment is very varied and of great importance is their prevention. The application of ozone therapy in this pathology has been demonstrated to be very useful, economic and necessary in the field of the Angiology. The aim of this study is to evaluate the efficacy and tolerance of ozone therapy in out-patients suffering of vein-lymphatic insufficiency in the period of one year. Seven hundred and seventy patients were involved in this study. Ozone was applied daily, by rectal (ozone concentration of 40 mg/L and 200 mL) and local administration (using plastic bags), during 15 sessions. The results demonstrated the cure of the lymphangitis and a good and rapid cicatrization of the ulcers. The treatment was evaluated as satisfactory in more than 80 %, with a significant decrease in the number of relapses. No side effects were observed in this study.